Customer satisfaction optimization: Impact of PLN mobile application and price in the context of PT. PLN Palembang services - Rahayu, Sri; Mahrom, Yudha; Helmi, Sulaiman (Edelweiss Applied Science and Technology, 2024)
This study aims to evaluate the effect of the PLN Mobile application and price on customer satisfaction at PT. PLN (Persero) UP3 Palembang ULP Rivai. This study also examines the role of price as a mediating variable in the relationship between the PLN Mobile application and customer satisfaction. The method used in this study is a quantitative approach with data analysis using Partial Least Squares Structural Equation Modeling (PLS-SEM). Primary data were collected through a survey involving 100 PLN Mobile customer respondents. The results of the analysis show that the PLN Mobile application has a positive and significant effect on customer satisfaction, with a path coefficient of 5.588 and a p-value <0.001. Price also has a significant effect on customer satisfaction with a path coefficient of 4.434 and a p-value <0.001. Furthermore, the indirect effect analysis revealed that price functions as a partial mediating variable between the PLN Mobile application and customer satisfaction, with a path coefficient of 3.513 and a p-value <0.001. These findings indicate that the PLN Mobile application and price directly affect customer satisfaction, and price plays an important role in strengthening the influence of the PLN Mobile application on satisfaction. Based on these results, it is recommended that PT. PLN continues to optimize the features and services of the PLN Mobile application to improve customer satisfaction and consider competitive pricing strategies. This study also suggests further studies to explore other factors that may affect customer satisfaction in the public service sector.